2014
DOI: 10.1002/humu.22617
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Exome Sequencing to Elucidate the Genetic Basis of Likely Recessive Disorders in Consanguineous Families

Abstract: Rare, atypical, and undiagnosed autosomal-recessive disorders frequently occur in the offspring of consanguineous couples. Current routine diagnostic genetic tests fail to establish a diagnosis in many cases. We employed exome sequencing to identify the underlying molecular defects in patients with unresolved but putatively autosomal-recessive disorders in consanguineous families and postulated that the pathogenic variants would reside within homozygous regions. Fifty consanguineous families participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 43 publications
3
70
0
Order By: Relevance
“…One previous large-scale clinical WES study reported that 5% of patients with a molecular diagnosis had two underlying single-gene disorders. 5 Another study in patients from consanguineous families reported a slightly higher rate (one out of 18), 20 which may be an underestimate given the identified variants only partially explained the clinical phenotype in two families. It needs to be noted that both estimates were influenced by indication for WES as well as previous knowledge about the identified variants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One previous large-scale clinical WES study reported that 5% of patients with a molecular diagnosis had two underlying single-gene disorders. 5 Another study in patients from consanguineous families reported a slightly higher rate (one out of 18), 20 which may be an underestimate given the identified variants only partially explained the clinical phenotype in two families. It needs to be noted that both estimates were influenced by indication for WES as well as previous knowledge about the identified variants.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of clinical WES and whole-genome sequencing have previously reported on patients with phenotypes arising from two, but not three, independent single-gene disorders. 4,5,[18][19][20] We propose that a sizeable proportion of the presumed monogenic diseases of yet unknown origin may in fact be due to clustering of several single-gene disorders. One previous large-scale clinical WES study reported that 5% of patients with a molecular diagnosis had two underlying single-gene disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the variants were filtered manually using the criteria described in previous studies. 11 As an initial filter in the target region of each family, we included all homozygous exonic and splicing variants (±6 bp of the intron-exon boundary) and excluded all synonymous variants, which are not in the splicing regions. We selected variants with a minor allele frequency o0.02 in the Exome Aggregation Consortium (ExAC) (http://exac.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…8 The combination of homozygosity mapping and exome sequencing is a powerful and cost-effective tool for molecular diagnosis and discovery of novel genes in families with suspected autosomal recessive disorders. [9][10][11][12][13] Using this approach, we studied two unrelated Pakistani consanguineous ID families, and identified two different homozygous missense variants in LINGO1 (leucine-rich repeat and immunoglobulin domain containing 1) that are likely to cause the intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…WGS and WES for Mendelian Disease Gene Discovery and Clinical Genetic Diagnosis WES, WGS, or targeted NGS sequencing of mapped candidate regions have quickly become the most widely used approaches for disease gene discovery, for which they have been highly successful (Bamshad et al 2011;Gilissen et al 2012Gilissen et al , 2014Beaulieu et al 2014;Dyment et al 2014;Makrythanasis et al 2014;Rios and Delgado 2014). This has resulted in a sharp increase in recent years in the number of Mendelian disorders for which the genetic basis is now known, from about 3000 a few years ago to a currently estimated approximately 4600 (Xue et al 2014), and this number continues to rise.…”
Section: Applications Of Diagnostic Sequencing In the Adult And Pediamentioning
confidence: 99%